Pengaruh Likuiditas, Leverage, Times Interest Earne Ratio, Pertumbuhan Penjualan Dan Ukuran Perusahaan Terhadap Profitabilitas Pada Perusahaan Property Dan Real Estate Yang Terdaftar Di BEI Periode 2015-2019 - Emi Ita Bonita Simatupang; Veronica Yulinar Ernita; Bonifasya Silalahi; Dina Rosalina; Maya Sabirina Panggabean (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
Economic conditions in Indonesia are currently in a fairly good development period, this can be seen from the number of companies that are growing and continuing to develop, one of which is manufacturing companies. This study uses a sample of 95 property and real stated companies by analyzing the performance of financial statements that have been audited by public accountants for the period 2015-2019. This study uses secondary data with a purposive sampling method. The method of analysis uses multiple linear regression methods. The results of this study indicate that simultaneously liquidity, leverage, times interest earned ratio, sales growth and company size have a significant effect on profitability. Partially, the variable leverage, times interest earned ratio, and sales growth have no effect on profitability. Meanwhile, working capital turnover has a negative and significant effect on profitability. And the liquidity ratio and size have positive and significant effect on protability. The coefficient of determination test results obtained an adjusted R square value 0f 0,247 or 24,7 percent, which means that the dependent variable, namely profitability, can be explained by variations of the three independent variables, namely cash turnover , working capital turnover and current ratio of 24,7percent, while the remaining 75,3 percent is explained by other factors not examined in this study. Keywords : Liqudity, Leverage, Times Interest Earned Ratio, Sales Growth, Company Size and Profitability.